I Want a Savior, Not a Victim. The Impact of Media Representations of the EU and Economic Shocks on Citizens' Supportive Attitudes on the European Integration. (12th February 2018) - Koehler, Christina; Weber, Mathias; Quiring, Oliver
Abstract: The Euro crisis substantially diminished citizens' support for the European integration. Therefore, we intend to analyze the independent effects of both the depiction of the Euro crisis in national news media and macroeconomic contexts on citizens' support for a deeper integration. Based on a combination of Eurobarometer data, results from a content analysis, and data on the economic performance of citizens' home regions, we show that presenting the European Union (EU) as a victim impedes citizens' supportive attitudes concerning the European integration, whereas depicting the EU as responsible for solving the crisis has a strengthening effect. Additionally, sharp economic developments in citizens' home regions also have significant effects on their prointegration attitudes, suggesting a differential influence of close and remote economic indicators.